40 MAGNETIC RESONANCE IMAGING FEATURES OF LIMB-LOCALIZED POLYARTERITIS NODOSA. Issue 1 (1st January 2007) - Cross, J.; Nasser, W. N.; Carbone, L. C.
Abstract : Purpose: The purpose of this study is to describe a case of localized polyarteritis nodosa (PAN). Materials and Methods: Case study including medical history, physical examination, laboratory and radiographic reports of a 51-year-old black male who presented to the Veterans Affairs Medical Center, Memphis, TN, with lower limb myalgias. Results: The patient's history was significant for 2 months of intermittent bilateral lower extremity pain and swelling associated with subjective fevers. Admission physical examination was notable for tenderness to calf muscles bilaterally, with no dermatologic lesions. Laboratory studies revealed elevated acute-phase reactants (CRP 344.2 mg/L (normal 0-4.9), ESR 112 mm/h (normal < 20), with normal muscle enzymes. Blood, urine, cerebrospinal fluid cultures and PPD, HIV, RPR, hepatitis A, B, and C panels, FANA, rheumatoid factor, and ANCA were negative. On hospital day 11, he developed right arm dysesthesias and lower leg weakness. MRI of his lower extremities revealed bilateral gastronemius and soleus muscles enhancement with edema. Sural nerve biopsy was consistent with PAN. Treatment with steroids resulted in improvement in myalgias; however, at the 5-month follow-up he has had progressive left lower extremity weakness and dysesthesias despite continued steroid use and two courses of cyclophosphamide. Conclusion: Calf muscle myalgias may rarely be the presenting feature of PAN, and this does not have a benign course. MRI may be useful in the diagnosis of limb-localized PAN.